The “unnatural” history of colorectal cancer in Lynch syndrome: lessons from colonoscopy surveillance - Ahadova, Aysel; Seppälä, Toni T.; Engel, Christoph; Gallon, Richard; Burn, John; Holinski-Feder, Elke; Steinke-Lange, Verena; Möslein, Gabriela; Nielsen, Maartje; Ten Broeke, Sanne W.; Laghi, Luigi; Dominguez-Valentin, Mev; et al. (International journal of cancer, 2021)
Individuals with Lynch syndrome (LS), one of the most common inherited cancer syndromes, are at increased risk of developing malignancies, in particular colorectal cancer (CRC). Regular colonoscopy with polypectomy is recommended to reduce CRC risk in LS individuals.